PELAKSANAAN PERNIKAHAN MELALUI WALI HAKIM DI KUA LECES KABUPATEN PROBOLINGGO - Imanuddin Abil Fida; Nur Aini Fitriawati (LPPM STAI Muhammadiyah Probolinggo, 2021)
Marriage is a sacred union between a man and a woman as consecrated by religion, with a noble purpose and purpose. Marriage is intended to bring about a happy, eternal family (home) surrounded by feelings of love, love, and peace between its members. To perform marriage must be met with the legal conditions for both bridegroom and bride, one of the marital requirements for the bride and groom. The status of a guardian is as important as it is known that the legal guardian of a woman is the guardian of nasab. In reality in Indonesia the ijab Kabul in marriage is often performed by religious affairs (cu) officials. This article speaks about marriage held in religious office by religious affairs in Leces Probolinggo